Analysis of Data on the Audiovisual Narrative of the YouTuber Ariana Bolo Arce During 2021 - Andahua-Inuma, Marcela Isabel (2024)
This research analyzes the perception of the Audiovisual Narrative of the restaurant segment of Ariana Bolo Arce's YouTube channel in 2021. Our objective is to determine the audience's perception of the image and sound elements of the restaurant segment of the aforementioned channel. Therefore, the qualitative methodology, the case study method, as well as observation and interview techniques were used. In addition, an observation sheet was used to find the most outstanding audiovisual elements, such as Angulation, Shots, Lighting, and Soundtrack. At the same time, interviews were applied to collect the perceptions of people from 18 to 25 years old who have been subscribed for more than 2 years to the channel and live in Comas, Lima, Peru. The results were systematized through data triangulation. The research showed that the perception of the Audiovisual Narrative of Ariana Bolo Arce’s YouTube channel varies in meaning according to the experiences of her followers.